Lymphoid differentiation pathways can be traced by TCR delta rearrangements - Fronková, Eva; Krejcí, Ondrej; Kalina, Tomás; Horváth, Ondrej; Trka, Jan; Hrusák, Ondrej (Journal of immunology (Baltimore, Md., 2005)
TCR gene rearrangement generates diversity of T lymphocytes by V(D)J recombination. Ig genes are rearranged in B cells using the same enzyme machinery. TCRD (TCR delta) genes are frequently incompletely rearranged in B precursor leukemias and recently were found in a significant portion of physiological B lymphocytes. Incomplete TCRD rearrangements (V-D) thus serve as natural indicators of previous V(D)J recombinase activity. Functional V(D)J recombinase has recently been found in murine NK precursors. We tested whether physiological NK cells and other leukocyte subpopulations contained TCR rearrangements in humans. This would provide evidence that V(D)J recombinase was active in the ancestry cells and suggest common pathways among the positive cell types. TCRD were rearranged in 3.2-36% of NK cells but not in nonlymphoid leukocytes. The previously known phenomenon of TCRD transcription in NK cells is a possible mechanism that maintains the chromatin open at the TCRD locus. In comparison, TCRG rearrangements were frequent in T cells, low to negative in B and NK cells, and negative in nonlymphoid cells, suggesting a tighter control of TCRG. Levels of TCRD rearrangements were similar among the B lymphocyte subsets (B1-B2, naive-memory). In conclusion, human NK cells pass through a differentiation step with active V(D)J recombinase similar to T and B lymphocytes and unlike nonlymphoid leukocytes. This contradicts recent challenges to the concept of separate lymphoid and myeloid differentiation.
Keywords: buňky HT-29; VDJ Recombinases; sekvence nukleotidů; Cell Line; polymerázová řetězová reakce; Cell Line, Tumor; Cell Lineage; genová přestavba - gama řetězec receptoru antigenů T-buněk; Gene Rearrangement, delta-Chain T-Cell Antigen Receptor; Sequence Analysis, DNA; buněčná diferenciace; sekvenční analýza DNA; Lymphocyte Subsets; molekulární sekvence - údaje; párování bází; Base Pairing; buněčný rodokmen; podskupiny B-lymfocytů; HeLa buňky; genetické markery; lidé; HeLa Cells; Humans; buňky NK; genová přestavba - delta řetězec receptoru antigenů T-buněk; HT29 Cells; buněčné linie; B-Lymphocyte Subsets; Molecular Sequence Data; VDJ-rekombinasy; Base Sequence; Polymerase Chain Reaction; nádorové buněčné linie; Killer Cells, Natural; Genetic Markers; podskupiny lymfocytů; Cell Differentiation; Gene Rearrangement, gamma-Chain T-Cell Antigen Receptor